Variation among gari samples of some yellow cassava (Manihot esculenta Crantz) varieties for change in color during storage - Olasanmi B; Udemba IO; Iluebbey P (Global Journal of Ecology - Peertechz Publications, 2022)
Carotenoids in bio-fortified gari are degraded by light and oxidation during storage resulting in fading of their yellow color. In this study, gari from yellow-root (bio-fortified) cassava varieties (YCVs) were evaluated for color change during storage in two seasons. About 400 g of fresh gari samples of five YCVs (IITA-TMSI011368, IITA-TMSI011371, IITA-TMSI011412, IITA-TMSI070539 and IITA-TMS-I070593) and white-root variety (TMEB419-check) were packaged in transparent plastics to ensure exposure to light. The samples were evaluated monthly for color change using a chart with a scale of 1 (white) to 8 (pink) for 12 months in each season. Data collected were subjected to ANOVA, descriptive and correlation analyses. Reduction in yellow color intensity was observed among the yellow gari samples in the first month from average of 4.40 to 3.53 representing about 20% decrease. At 12 months after processing, varieties IITA-TMSI011368 and IITA-TMSI011371 had the highest (68%) and least (58%) yellow pigment retention, respectively. There was significant variation among the varieties for gari color change and yellow pigment retention over the storage period. Therefore, carotenoid content in bio-fortified gari depends on the cassava variety and storage period. These factors should be considered in future breeding program to improve cassava for carotenoid content.